Influence of Ga incorporation on photoinduced phenomena in Ge-S based glasses - Ledemi, Y. [UNESP]; Messaddeq, S. H. [UNESP]; Skhripachev, I. [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP] (Elsevier B.V., 2009)
To study the influence of Ga addition on photoinduced effect, GaGeS glasses with constant atomic ratio S/Ge = 2.6 have been prepared. Using Raman spectroscopy, we have reported the effect of Ga on the structural behavior of these glasses. An increase of the glass transition temperature T(g), the linear refractive index and the density have been observed with increasing gallium content. The photoinduced phenomena have been examined through the influence of time exposure and power density, when exposed to above light bandgap (3.53 eV). The correlation between photoinduced phenomena and Ga content in such glasses are shown hereby. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Raman scattering; Chalcogenides; Photoinduced effects